Penerapan Model Pullout bagi Peserta Didik Berkebutuhan Khusus di MIN 1 Magelang - Eko Yuniawan; Khoirul Inayah (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2025)
This study examines the implementation of the pullout model for students with special needs at MIN 1 Magelang, an Islamic elementary school in Central Java. Using descriptive qualitative methodology, data were collected through in-depth interviews, classroom observations, and authentic documentation from school principals, teachers, students with special needs, parents, and classmates. The findings reveal that 18 students with learning difficulties including slow learners, mild intellectual disabilities, cerebral palsy, low vision, autism, ADHD, and ADD successfully learn alongside regular students in mainstream classes while receiving specialized instruction in resource rooms during specific learning challenges. The pullout model proved effective in improving academic achievement, self-confidence, and learning motivation. Integration of Islamic religious values enhanced students' self-acceptance through understanding the concept of divine decree. Despite infrastructure limitations and lack of formal certification as an inclusive education provider, the school's success was driven by teachers' high commitment, strong leadership support, and active parental involvement. MIN 1 Magelang demonstrates significant potential as a sustainable faith-based inclusive education model for other madrasahs in Indonesia.